Is Sleep-Related Eating Disorder (SRED) a NREM Parasomnia or a Heterogenous Disease? - Nico Zobrist; Zhongxing Zhang; Ramin Khatami (Clinical and Translational Neuroscience, 2023)
Sleep-related eating disorder (SRED) is a relatively rare but probably underestimated disorder, where affected patients exhibit nocturnal eating episodes with impaired consciousness and subsequent amnesia. SRED has originally been classified as NREM (non-rapid eye movement) parasomnia, with an obviously high number of concomitant sleep disorders. We suggest that SRED may represent a heterogenous disease, based on accumulating data in recent studies. Some SRED patients may be better classified as sleep-related movement disorders with an underlying dopaminergic dysfunction. Hypnotic drugs may play a crucial role in triggering amnestic SRED in both parasomnic and sleep-related movement-disordered SRED.